Fixed point theorems on cone \(S\)-metric spaces using implicit relation - Saluja, G. S. (CUBO, A Mathematical Journal, 2020)
In this paper, we establish some fixed point theorems in the framework of cone \(S\)-metric spaces using implicit relation. Our results extend, unify and generalize several results from the current existing literature. Especially, they extend the corresponding results of Sedghi and Dung [24] to the setting of complete cone \(S\)-metric spaces.